Progress of MMP and AQP4 in neonatal hypoxia/ischemia‐induced brain edema. Issue 1 (28th March 2016) - Zhang, Zi‐Bin; Yu, Chang‐Yin
Abstract : Neonatal hypoxic‐ischemic encephalopathy (NHIE) caused by hypoxia‐ischemia (HI) in the prenatal and perinatal period is a major cause of morbidity and mortality in infants and children. As a common outcome after NHIE, cerebral edema, the mechanisms leading to excessive fluid accumulation in the brain, were poorly understood. In the present, matrix metalloproteinase (MMPs) and aquaporin proteins 4 (AQP4) had become the focus of research on the pathogenesis of neonatal cerebral edema. MMPs and AQP4 were involved in a variety of pathophysiological processes in neonates with ischemic injury. Therefore, understanding the molecular mechanisms of MMPs and AQP4 under cerebral edema may provide new insights into pathogenesis and treatment of HIE. In this review, we summarized the latest progress of MMP and AQP4 in HIE condition.